Effect of chronic diseases and the use of total prostheses on the flow and the buffer capacity of the saliva of the elderly - Costa Oliveira, Thaíze; Gonçalves Silva, Thamiris; Pando, Luzia Aparecida; Couto Assis, Wagner; Andrade Nunes, Lorena; Casotti, Cezar Augusto; Benemérita Alves Vilela, Alba (O Mundo da Saúde, 2019)
Reduction of salivary flow is often observed in the elderly. Considering the high prevalence of chronic diseases, edentulism and/or use of dental prostheses, this study aimed to evaluate the effect of chronic diseases and the use of prostheses on the flow and the buffer capacity of the saliva of the elderly. The elderly study participants were over 60 years old, living in the municipality of Jequié-BA. A form was used to obtain socio-demographic information, self-reported chronic diseases, alcohol and tobacco consumption. For the saliva collection, the stimulated salivation method was performed using a sterile chewing latex. The saliva collected from each individual was measured to obtain the salivary flow per minute. The buffer capacity was obtained by adding 3 mL of Hydrochloric Acid to 1 mL of saliva. A pH meter was used to measure salivary pH before and after addition of the acid. It was identified that among the elderly, 44.06% (26) demonstrated hyposalivation (stimulated saliva ≤ 0.7 mL/min) and 27.11% (16) low salivary flow (0.7 to 1.0 mL/min). The use of total prostheses and the presence of diabetes mellitus displayed a positive correlation with salivary flow. It is suggested that the use of prostheses reduces the tactile stimuli that contribute to the regulation of the salivary pathways. Arterial hypertension, alcohol and tobacco use did not demonstrate a significant correlation with salivary flow and buffer capacity. It was concluded that the use of total dental prostheses and diabetes mellitus interfere in the salivary flow of the elderly.